Need-Supportive and Need-Thwarting Teacher Behavior: Their Importance to Boys’ and Girls’ Academic Engagement and Procrastination Behavior - Opdenakker, Marie-Christine (Frontiers in Psychology, 2021)
Motivation plays an important role in students’ school behavior and research has established that students’ learning environment experiences such as teachers’ behavior towards them contribute to their motivation and behavior at school. Self-determination theory offers an interesting frame of reference in the study of the relationship between students’ learning experiences at school and their school behavior. Considering three basic psychological needs (the need for autonomy, competence and relatedness), self-determination theory points to the importance of nutriments and support in the social environment in order to allow growth in motivation, engagement and (psychological) well-functioning. In addition, thwarting these needs is supposed to contribute to maladaptive functioning. Teachers can play an important role in the fulfillment of students’ basic psychological needs by delivering support (autonomy support, structure, involvement); however, controlling instructional behaviour, chaos in the classroom, and teacher rejection and neglect, are supposed to be a treat to the fulfilment of students’ basic psychological needs. In the current innovative longitudinal study, teachers’ need-supportive behavior as well as teachers’ thwart of these needs are considered and their relationship with students’ academic engagement (adaptive functioning) and procrastination behavior (maladaptive functioning) is studied. In addition, attention is paid to differential effects of teachers’ behavior with regard to boys and girls. Participants were 566 students belonging to 20 Mathematics/English grade-1 secondary education classes in The Netherlands. Multilevel analyses revealed evidence for the importance of both teachers’ need-supportive and teachers’ need-thwarting behavior in relation to students’ academic engagement and procrastination behavior. In addition, findings revealed that teachers’ need-supportive behavior is more important for students’ academic engagement (adaptive functioning), while teachers’ need-thwarting behavior has larger effects on students’ procrastination behavior (maladaptive functioning). Furthermore, evidence was found that boys often seemed to be more sensitive to their teachers’ behavior than girls. Findings highlight the importance of both teachers’ need-supportive and teachers’ need-thwarting behavior in daily classrooms and contribute to deepen our insight in and understanding of factors leading to adaptive and maladaptive functioning of boys and girls in relation to learning tasks at school.